Southern man : a novel - Iles, Greg (Penn Cage, 2024)
"Fifteen years after the events of the Natchez Burning trilogy, Penn Cage is alone. Nearly all his loved ones are dead, his old allies gone. But Penn's self-imposed exile comes to an abrupt end when a brawl at a Bienville music festival triggers a shooting--one that nearly takes the life of his daughter Annie. Before the stunned populace can process the tragedy, an arsonist begins torching antebellum plantation homes in Bienville. When an unknown Black group claims the fires as acts of justice, panic ensues, driving the Mississippi River town to the brink of war"--